La reinserción integral de las o los ciudadanos con pasado judicial, a través de la protección de datos públicos - Jurado Meza, Christian Alex (2017)
The present research project notes the deficiencies of the legal system of the country. Since 2009, the Council of the Judiciary was created in its structuring, implementing the SATJE computer system, which is used to search judicial processes. Thousands of citizens who have reported that their rights are violated by following their personal data on this page, leaves them in total violation since, their data as: names, surnames and cedula, they leave as a database next to the judicial process Which has been immersed……